NirA Is an Alternative Nitrite Reductase from Pseudomonas aeruginosa with Potential as an Antivirulence Target - Fenn, Samuel (mBio, 2021)
The opportunistic pathogen Pseudomonas aeruginosa produces an arsenal of virulence factors causing a wide range of diseases in multiple hosts and is difficult to eradicate due to its intrinsic resistance to antibiotics. With the antibacterial pipeline drying up, antivirulence therapy has become an attractive alternative strategy to the traditional use of antibiotics to treat P. aeruginosa infections. To identify P. aeruginosa genes required for virulence in multiple hosts, a random library of Tn5 mutants in strain PAO1-L was previously screened in vitro for those showing pleiotropic effects in the production of virulence phenotypes. Using this strategy, we identified a Tn5 mutant with an insertion in PA4130 showing reduced levels of a number of virulence traits in vitro. Construction of an isogenic mutant in this gene presented results similar to those for the Tn5 mutant. Furthermore, the PA4130 isogenic mutant showed substantial attenuation in disease models of Drosophila melanogaster and Caenorhabditis elegans as well as reduced toxicity in human cell lines. Mice infected with this mutant demonstrated an 80% increased survival rate in acute and agar bead lung infection models. PA4130 codes for a protein with homology to nitrite and sulfite reductases. Overexpression of PA4130 in the presence of the siroheme synthase CysG enabled its purification as a soluble protein. Methyl viologen oxidation assays with purified PA4130 showed that this enzyme is a nitrite reductase operating in a ferredoxin-dependent manner. The preference for nitrite and production of ammonium revealed that PA4130 is an ammonia:ferredoxin nitrite reductase and hence was named NirA.